Measuring disease progression in primary lateral sclerosis. (2nd November 2020) - Gilmore, Madison; Elman, Lauren; Babu, Suma; Andres, Patricia; Floeter, Mary Kay
Abstract: Quantitative measures of disease severity are essential outcome measures for clinical trials. The slow progression of disease in primary lateral sclerosis (PLS) requires clinical measures that are sensitive to changes occurring within the time frame of a clinical trial. Proposed clinical outcome measures include the PLS functional rating scale (PLSFRS), burden scores derived from clinical examination findings, and quantitative measures of motor performance. The PLSFRS has good inter-rater reliability and showed greater longitudinal change over 6- and 12-months compared to the revised ALS functional rating scale. Examination-based upper motor neuron burden (UMNB) scales also have good reliability, and longitudinal studies are in process. Quantitative measures of strength, dexterity, gait, and speech have the potential to provide objective and precise measures of clinical change, but have been the least studied in persons with PLS.